A novel bispecific antibody drug conjugate targeting HER2 and HER3 with potent therapeutic efficacy against breast cancer - Zong Hui-fang; Li Xi; Han Lei; Wang Lei; Liu Jun-jun; Yue Ya-li; Chen Jie; Ke Yong; Jiang Hua; Xie Yue-qing; Zhang Bao-hong; Zhu Jian-wei (Acta Pharmacologica Sinica, 2024)
Antibody drug conjugate (ADC) therapy has become one of the most promising approaches in cancer immunotherapy. Bispecific targeting could enhance the efficacy and safety of ADC by improving its specificity, affinity and internalization. In this study we constructed a HER2/HER3-targeting bispecific ADC (BsADC) and characterized its physiochemical properties, target specificity and internalization in vitro, and assessed its anti-tumor activities in breast cancer cell lines and in animal models. The HER2/HER3-targeting BsADC had a drug to antibody ratio (DAR) of 2.89, displayed a high selectivity against the target JIMT-1 breast cancer cells in vitro, as well as a slightly higher level of internalization than HER2- or HER3-monospecific ADCs. More importantly, the bispecific ADC potently inhibited the viability of MCF7, JIMT-1, BT474, BxPC-3 and SKOV-3 cancer cells in vitro. In JIMT-1 breast cancer xenograft mice, a single injection of bispecific ADC (3 mg/kg, i.v.) significantly inhibited the tumor growth with an efficacy comparable to that caused by combined injection of HER2 and HER3-monospecific ADCs (3 mg/kg for each). Our study demonstrates that the bispecific ADC concept can be applied to development of more potent new cancer therapeutics than the monospecific ADCs.